UVios / Nazura Mohamad Najib and Norarifah Ali - Mohamad Najib, Nazura; Ali, Norarifah (Faculty of Art and Design, 2021)
This new-norm era which has pros and cons, has made us a new generation that can be independent and can adapt with a new world. A common situation which we can picture is when we start to shop online. From a research that has been made, millennials (18 – 35 years old) are the age group that make shopping online most often. When a parcel packaging has arrived at the directed destination, most of them do not know how to take safety precautions. Sometimes they just straightly unbox the parcels and wash their hands. We cannot guarantee that the parcel is safe in terms of its hygiene aspect. Moreover, we have to be extra paranoid these days because of Covid-19 virus. In that case, UVios can help us to be more hygienic and save our time without having to disinfect the parcel using sanitizer first. UVios is a parcel disinfecting tool that uses UV-C based technology for users at home to prevent any virus infection. How does this product actually work? When a courier service arrives in front of our house, UVios that has been turned on is placed there and the courier service staff has to put the parcel (not more than 315mm x 315mm x 360mm) inside the product and it will start to gush out UV light. The light is specially designed to disinfect surfaces using UltraViolet-C which is used in hospitals to disinfect their tools, nail salons to harden their nail polish and baby bottle sterilizer used by moms at their homes. UVios helps these users especially housewives and youngsters to make their packages safe and free from any kind of virus including Cov-Sars-2. Therefore, they no longer have to waste time by doing virus prevention measures such as washing hands with soap, wearing hand sanitizer all the time or spraying their parcel using do-it-yourself sanitizer (a mixture of bleach and water) at every corner of the parcel.